DATA-DRIVEN DECISIONS IN THE MANAGEMENT PROCESS OF THE ORGANIZATION - Gevorgyan, Anahit (Modern Psychology, 2023)
Nowadays, to maintain and develop the normal activities of the organization, as well as staff management, it is important to follow innovative developments in the fields of human resource management and information technology, as well as apply modern approaches in the process of personnel and organization management. The theoretical analysis aimed at revealing the development of People analytics as an interdisciplinary field that allows using data collected from various sources and the results of their analysis, its’ main features and the ways of application in order to improve the personnel and organizational management. People analytics is a data-driven approach to personnel and organizational management process improvement, which enables us to use data collected from various sources in the decision-making process. The article describes the origin and development of people analytics, the types of data analysis and possibilities of using personnel and data analysis in various human resources management processes, citing successful stories in several large organizations as an example. The use of people analysis tools and artificial intelligence allows not only to derive HR metrics and gain insights about the current state of the organization, but also to perform predictive analytics, understand the dynamics and direction of development, and develop a strategy to achieve the desired goal. The results of the theoretical analysis and described examples indicate the importance of using the capabilities of people analytics in the field of human resources management. It allows us to make data-driven decisions, organize the work process more effectively, identify the existing problems in the field of company’s HRM and develop strategy to overcome these issues and develop the organization.